Myc derived circRNA promotes triple-negative breast cancer progression via reprogramming fatty acid metabolism - Shengting Wang; Yufang Wang; Yue Wang; Qian Li; Kaixuan Zeng; Xiaoming Li; Xinghua Feng (Discover Oncology, 2023)
Abstract Myc is a well-known proto-oncogene that is frequently amplified and activated in breast cancer, especially in triple-negative breast cancer (TNBC). However, the role of circular RNA (circRNA) generated by Myc remains unclear. Herein, we found that circMyc (hsa_circ_0085533) was remarkably upregulated in TNBC tissues and cell lines, which was attributed to gene amplification. Genetic knockdown of circMyc mediated by lentiviral vector significantly inhibited TNBC cell proliferation and invasion. Importantly, circMyc increased cellular triglycerides, cholesterols and lipid droplet contents. CircMyc was detected in both cytoplasm and nucleus, cytoplasmic circMyc could directly bind to HuR protein, facilitating the binding of HuR to SREBP1 mRNA, resulting in increasing SREBP1 mRNA stability. Nuclear circMyc bound to Myc protein, facilitating the occupation of Myc on SREBP1 promoter, leading to increasing SREBP1 transcription. As a result, the elevated SREBP1 increased the expression of its downstream lipogenic enzymes, enhancing lipogenesis and TNBC progression. Moreover, the orthotopic xenograft model showed that depletion of circMyc markedly inhibited lipogenesis and reduced tumor size. Clinically, high circMyc was closely related to larger tumor volume, later clinical stage and lymph node metastasis, functioning as an adverse prognostic factor. Collectively, our findings characterize a novel Myc-derived circRNA controlling TNBC tumorigenesis via regulation of metabolic reprogramming, implying a promising therapeutic target.